Optic chiasm involvement in AQP-4 antibody–positive NMO and MOG antibody–associated disorder. (January 2022) - Tajfirouz, Deena; Padungkiatsagul, Tanyatuth; Beres, Shannon; Moss, Heather E; Pittock, Sean; Flanagan, Eoin; Kunchok, Amy; Shah, Shailee; Bhatti, M Tariq; Chen, John J
Background: Optic neuritis (ON) is often the presenting symptom in inflammatory central nervous system demyelinating disorders. Objective: To compare the frequency and pattern of optic chiasm involvement in patients with aquaporin-4-immunoglobulin G (AQP4-IgG)-associated ON to patients with myelin oligodendrocyte glycoprotein-immunoglobulin G (MOG-IgG)-associated ON. Methods: Retrospective review of all patients evaluated at Mayo Clinic, Stanford University and Ramathibodi Hospital who were found to have: (1) ON, (2) either MOG-IgG or AQP4-IgG by cell-based assay, and (3) magnetic resonance imaging (MRI) at the time of ON. MRI was reviewed for contrast enhancement of the optic chiasm and the pattern of involvement. Results: One hundred and fifty-four patients (74 AQP4-IgG and 80 MOG-IgG) were included. Among patients with AQP4-IgG-ON, 20% had chiasmal involvement, compared with 16% of patients with MOG-IgG-ON ( p = 0.66). In patients with chiasmal involvement, longitudinally extensive optic nerve enhancement (from orbit extending to chiasm) was identified in 54% of MOG-IgG-ON patients, compared with 7% of AQP4-IgG-ON patients ( p = 0.01). Conclusion: Chiasmal involvement of MOG-IgG-ON and AQP4-IgG-ON occur at more similar frequencies than previously reported. Furthermore, MOG-IgG-ON chiasmal involvement is more likely to be part of a longitudinally extensive optic nerve lesion.